2021
DOI: 10.3390/nu13041380
|View full text |Cite
|
Sign up to set email alerts
|

Diet Quality of Malaysians across Lifespan: A Scoping Review of Evidence in a Multi-Ethnic Population

Abstract: Malaysia is a rapidly developing economy experiencing a nutrition transition. It suffers from a double burden of over- and undernutrition, making it essential to understand diet quality in the population. In this scoping review, we have collated the existing literature on Malaysian diet quality, including factors that influence it, and the association between diet quality and health outcomes across the lifespan of Malaysians. Overall, diet quality was poor in all age groups studied. The Healthy Eating Index (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 45 publications
(58 reference statements)
0
5
1
Order By: Relevance
“…Good-quality diet plays an important role in improving the overall health, growth and academic performance of students 19. Despite this, different studies in both developed and developing countries reported poor-quality diets of adolescents 6 31. Similarly, only 24.7% (95% CI: 21.7%, 27.7%) of school-going adolescents in this study had good-quality diets.…”
Section: Discussioncontrasting
confidence: 81%
“…Good-quality diet plays an important role in improving the overall health, growth and academic performance of students 19. Despite this, different studies in both developed and developing countries reported poor-quality diets of adolescents 6 31. Similarly, only 24.7% (95% CI: 21.7%, 27.7%) of school-going adolescents in this study had good-quality diets.…”
Section: Discussioncontrasting
confidence: 81%
“…30,136,137 For example, it has been reported that those of a higher SES consume a less healthy diet and are at a higher risk of overweight and obesity relative to those with a lower SES in Vietnam 137,138 and Indonesia. 139 Conversely, within HICs, such as Japan and South Korea, 138,140 and UMICs, such as China, Malaysia, and Thailand, 134,[141][142][143] where the nutrition transition is further advanced, those with a lower SES have been found to consume a less healthy diet and are at a higher risk of overweight and obesity compared to those with a higher SES. Given the equity implications of the nutrition transition it is important that governments implement food and nutrition policies that reach and impact everyone in the population, particularly those with more limited social and economic resources.…”
Section: Discussionmentioning
confidence: 99%
“…Diet quality assessment of the population can be generally regarded to be based on (1) food and food groups, (2) nutrients, and (3) combinations of both (Table 2) [17]. Combination indices are generally more common, which was also evident in our review [34,35,[39][40][41][42]45,47].…”
Section: Diet Quality Measuresmentioning
confidence: 75%
“…Various dietary metrics have been developed and used to assess diet quality, such as Diet Quality Index (DQI), Diet Quality Index-International (DQI-I), Healthy Eating Index (HEI), Alternative Healthy Eating Index (AHEI), Food Pyramid Index (FPI), Food Variety Score (FVS), and others [16][17][18]. Some developing countries have tailored the diet quality scores to align with their country-specific recommended nutrient intake and dietary guidelines [19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation